06 The Mediating Role of Social Support on the Relationship Between Perceived Locus of Control, Quality Of Life And Depression Among Male And Female Migration Patient (Journal of Gender and Social Issues, 2018)
The aim of conducting the present study was to investigate the relationship between locus of control, quality of life and depression among migraine patients. The sample of N=100 (males/females) migraine patients, age ranging between 25-50 were taken from Benazir Bhutto Hospital and District Head Quarter Hospital located in Rawalpindi. In order to measure locus of control, quality of life, depression and social support, the Urdu version of TheMultidimensional Health Locus of Control Scale (MHLC), The Quality Of LifeScale (WHOQOL), The Beck's Depression Inventory (BDI) and The Multidimensional Scale of Perceived Social Support (MSPSS) were used. After the data collection the data was analyzed by SPSS version 21. The findings of this study revealed that a negative relationship exists between social support and depression. Results also showed that there is a positive relationship between quality of life and social support...
Keywords: Social Support; Locus of Control; Depression; Quality of Life and Migraine Patients